Analysis of the Impact of Low Self-Confidence on Early Childhood Social Development - Lailatul Mubarokah; Ezif Rizqi Imtihana (Manunggal Halim Jaya, 2026)
This study aims to examine the effect of low self-confidence on the social development of early childhood at TK Tri Kusumo. A quantitative approach with a correlational design was employed to analyze the relationship between low self-confidence (X) and children’s social development (Y). The sample consisted of 25 children aged 4–6 years selected through total sampling. Data were collected using observation and structured questionnaires based on predefined indicators of both variables. The data were analyzed using the Pearson Product Moment correlation test. The findings revealed that the level of low self-confidence among children was relatively high, as indicated by behaviors such as shyness, hesitation in speaking, and reluctance to perform in front of others. Meanwhile, children’s social development was found to be suboptimal, particularly in communication, interaction, and cooperation skills. The correlation analysis showed a coefficient value of r = -0.67, indicating a strong negative relationship between low self-confidence and social development. This suggests that higher levels of low self-confidence are associated with lower levels of social development. Therefore, enhancing children’s self-confidence through supportive learning environments and appropriate stimulation from teachers and parents is essential to optimize their social development.